The morpho-semantics of compound words in Sepedi - Maboa, Rachel Mmapitso (My University, 2022)
The prime goal of this study is to explore, form and analyse the semantic content of compound words in Sepedi. The study used the qualitative method. Data were collected using participant observations from various written sources and it was analysed through Content Analysis. The Theory of Construction Morphology was tested on endocentric, exocentric, and copulative compound words to locate the headedness of Sepedi compound words. The study revealed that the head of compound words can be located on the nominal prefix, left-hand side, right-hand side, on both nominal prefixes and it can be determined outside of the compound word for metaphoric exocentric nominal compounds. Furthermore, because of the role noun class prefixes play on determining the head of compound words, the study found that Sepedi compound words are nominals. The formation of Sepedi compound words involves the combination of different word aspects such as objects concords, deverbatives, verbal roots, stems, suffixal endings, and lexical categories such as nouns, Adjectives, and verbs. The resultant compound word of these combinations always results in a compound noun. It was recommended that future researchers should investigate the semantic content of exocentric compound words in African languages, especially the Sepedi language. The study further highlighted that there is still a need for a study that looks at the influences of nominal prefixes on the headedness of compound words in Sepedi. Furthermore, the study recommended that to alleviate the gap of shortage of literature in Sepedi, future studies should focus on word formation processes in Sepedi.
Thesis (M.A. (Translation Studies and Linguistics)) -- University of Limpopo, 2022
Keywords: Semantic content; Compound words; Lexical categories; Endocentric; Exocentric; Copulative; Headless; Headedness; Prefixes; Nominals; Morphemes; Northern Sotho language -- Compound words; Northern Sotho language -- Morphemics; Northern Sotho language -- Semantics; Grammar, Comparative and general -- Morphology